The Challenges In The Development Of Bread Using Modified Cassava Flour (Mocaf) With Addition Of Roselle Calyces Powder - Azahari, Nur Amiera Kamilia (Universiti Sains Malaysia, 2020)
The aims of this comprehensive study were to review the current research development on functional bread, the application of modified cassava flour (MOCAF) as a wheat substitution in bakery products and to review the properties of Roselle calyces powder in bakery products. With the advancement in this current era, the interests for a healthier food has increased. Other than that, the consumption of bread has also increased as it is a convenience, which made the imports for wheat flour also became increasing. In order to tackle this problem, the development of bread using MOCAF with addition of Roselle calyces powder may serve as national food security as well as providing health benefits for human consumptions. MOCAF, which is produced by fermentation process of cassava roots possessed similar characteristic to wheat flour in terms of its appearance, aroma and taste. Besides that, fermentation process of cassava roots can also reduce the amount of hydrogen cyanide (HCN) and phytic acid that believed can cause toxicity to human if consume it without undergo processes. In addition, MOCAF is suitable for gluten intolerance people since it does not have gluten. However, there will be some drawbacks on producing bread using solely MOCAF since it could not form a good bread properties as well as lacking with bioactive compounds. Therefore, further research is essential to focus on the functional aspect as well as incorporating MOCAF a base ingredient in bread making. To make MOCAF bread to have functional properties, edible flowers can be added. Roselle is one of the edible flowers that contains high amount of phytochemicals mainly anthocyanins, that were recognized as to increase the functional properties of food products.